The installation of Prince Mangkubumi; Performing Javanese history - Bogaerts, Els (Wacana, Journal of the Humanities of Indonesia, 2016)
Representation of Javanese history in performance plays an important role in the self-characterization of the Special Region of Yogyakarta. It legitimizes the power of the rulers and strengthens the identity of the city and its inhabitants. The audiences know the stories and this is part of the fun. In the study of oral traditions it is essential to take these performances into account. In the stories featuring famous political figures from the history of Mataram and Yogyakarta, there is an intricate relationship between the written and the spoken word: all are based on both oral and written traditions and are performed 'orally'. Prince Mangkubumi, who was to become the first sultan of Yogyakarta in 1755, is one of the historical personages who are protagonists in various performance genres. Focusing on the tale of Prince Mangkubumi's accession to the throne, I shall reflect on how the televised kethoprak version combines a (written) text with a mediated (aural/visual) performance to present the story.